Library Automation: An Emerging Technology for State University and Colleges in Sulu Province - Shernahar K. Tahil (HM Publisher, 2022)
The library is one of the most important places in any academic institution and remains the primary source of information for students, teachers, and many others. This literature review aimed to describe technological advancement in the managing library. The breakthrough of technologies can help the library in various ways. Libraries need to adopt new technology that will allow them to operate and function efficiently and effectively, increasing their productivity and improving their user services without adding personnel. Fortunately, new technologies have developed barcode, digital libraries, quick response codes, and radio frequency identification (RFID) systems. Consequently, applying these technologies provides an end-to-end solution for easy library operation, such as borrowing and returning books, finding and locating books, and maintaining book records. The need to develop and enhance library services to meet users' demands is necessary.